Судові доручення щодо збирання доказів у цивільному судочинстві України - Сулейманова, Сусанна Рефатівна; Сулейманова, С. Р.; Suleimanova, Susanna R. (Херсон : Видавничий дім «Гельветика», 2019)
У статті викладено наукові результати аналізу інституту судових доручень щодо збирання доказів у цивільному судочинстві України, розкрито їх зміст відповідно до чинного законодавства і правозастосовчої практики, визначені параметри і перспективи розвитку. Сформульовано пропозиції до чинного законодавства відносно вдосконалення правового регулювання інституту судових доручень щодо збирання доказів.

The intensification of economic processes, the dynamics of social development, universal integration and globalization all have their natural consequence that the relations of the participants of the civil turnover are not confined within the territory of one city or region, but are formed at the interregional and sometimes international level. This inevitably leads to the courts having to consider disputes that have evidence beyond their territory. In these circumstances, the procedural tools and tools that make it possible to judicially examine such evidence in the region of their location are of particular importance. According to the rules of the Civil Procedure Code of Ukraine, such an instrument is a judicial instruction to commit certain procedural actions. The legal regulation of the institute of judicial orders in the civil judiciary of Ukraine sufficiently conditionally allows the existence of so-called “domestic” judicial orders and judicial orders “with foreign element”. “Domestic” judicial orders are judicial orders, which are forwarded by Ukrainian courts to Ukrainian courts in the territory of Ukraine within the Ukrainian judicial system. “Foreign element” judicial orders may be referred to as documents, documents, obtaining individual procedural actions in the territory of another state, or execution of foreign court orders, reflecting the procedure for bilateral appeals of Ukrainian courts to foreign courts or competent authorities of foreign countries. The rules on judicial orders by virtue of their fixation in the Code of Civil Procedure of Ukraine, which establish the rules of civil procedure in the courts of the general jurisdiction of Ukraine, confer powers to send binding orders only to courts that are part of the judicial system of Ukraine. Thus, outside the system of cooperation through court orders, all bodies and organizations that are not judicial bodies, including arbitration courts, remain. The article presents the scientific results of the analysis of the institution of court orders for the collection of evidence in the civil proceedings of Ukraine, their content is disclosed in accordance with current legislation and law enforcement practice, the parameters and development prospects are determined. Proposals are made to the current legislation regarding the improvement of the legal regulation of the institution of court orders for the collection of evidence.
Сулейманова С. Р. Судові доручення щодо збирання доказів у цивільному судочинстві України / С. Р. Сулейманова // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Херсон : Видавничий дім «Гельветика», 2019. – Вип. 34. – С. 67-73.
Keywords: судові доручення; докази; засоби доказування; цивільне судочинство; court orders; evidence; witness; civil proceedings; Research Subject Categories::LAW/JURISPRUDENCE